Animate to Harmony : the independent animator's guide to Toon Boom - Phillips, Adam. (New York : Focal Press, Taylor & Francis Group, 2015)
"Want to create studio-quality work and get noticed? Just coming off Flash and looking for a Toon Boom intro? Are you a traditional pencil-and-paper animator? From scene setup to the final render, learn how to navigate the Toon Boom interface to create animation that can be published on a variety of platforms and formats. Animate to Harmony guides you through Toon Boom's Animate, Animate Pro and Harmony programs, teaching you how to create high-quality 2D animation of all complexities. The main text focuses on features that are common across all three programs while "Advanced Techniques" boxes throughout the book elaborate on Pro and Harmony features, appealing to all levels of experience with any of the three main Toon Boom products"--
Cover Half Title Title Page Copyright Page Table of Contents Introduction Chapter 1 Interface Chapter 2 Tools Chapter 3 Animation Chapter 4 Effects Chapter 5 Camera Chapter 6 Audio Chapter 7 Rendering Appendix A Advanced Tools Appendix B Slightly Technical Stuff Index.
Includes index.
Keywords: Toon Boom animate; Computer animation